Graded vertical rectus tenotomy for small-angle cyclovertical strabismus in sagging eye syndrome. Issue 5 (25th August 2015) - Chaudhuri, Zia; Demer, Joseph L
Abstract : Background/aims: Graded vertical rectus tenotomy (GVRT) is postulated as effective for small-angle vertical heterotropia. We aimed to determine the dosing recommendations for GVRT in sagging eye syndrome (SES). Methods: This was a retrospective, observational study of surgical outcomes for GVRT from 2009 to 2014 in a single surgeon's academic practice. There were 37 (20 women) patients of average age 68±10 (SD) years with comitant or incomitant hypertropia ≤10Δ caused by SES. The main outcome measure was the dose–effect of GVRT required to correct intraoperative hypertropia. Results: Preoperative average central gaze hypertropia measured 4.7±2.2Δ. Three patients underwent repeat GVRT for residual or consecutive hypertropia, one undergoing it twice. All surgeries were analysed, increasing the total operations to 41. The inferior rectus tendon in the hypotropic eye was operated in 32 eyes, and the superior rectus tendon in the hypertropic eye in 9 eyes. Mean tenotomy was 68±19% of tendon width. Hypertropia was always eliminated intraoperatively by progressive GVRT. Mean hypertropia was 1.1±1.6Δ at average 93 days postoperatively. Linear regression demonstrated that 3–6Δ hypertropia correction requires 30%–90% graded tenotomy (R 2 =0.32, p<0.0001), but with substantial individual variability. Undercorrection necessitated reoperation in 10% of cases. Conclusion: GVRT precisely corrects hypertropia of up to 10Δ, but because of variable effect, it should be performed with intraoperative monitoring under topical anaesthesia.